Evaluasi Operasional dan Pemeliharaan Instalasi Pengolahan Air Limbah Industri Kimia PT. XYZ - Muchammad Ali Ma'shum Mujaddidi; Teguh Taruna Utama; Arqowi Pribadi (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
PT. XYZ is a company active in the chemical industry. Both its production and domestic activities generate waste. PT. XYZ has a waste water treatment plant (WWTP) that is in operation to treat the waste water produced. The treated wastewater is applied to the soil for irrigation of landscaping within the PT. XYZ industrial estate. The objective of this study is to evaluate the performance of the WWTP, particularly in terms of the operation and maintenance phases that affect its effectiveness. The standard operating procedures are based on the STP Guide: Design, Operation, and Maintenance by Ananth S. Kodavasa (2011), Book 3 SOP Asset Operation of UPTD Domestic Wastewater Management (2018), and Minister of Public Works Regulation No. 4 of 2020, Annex II. The WWTP operation and maintenance procedures include units such as grease trap, equalisation tank, mixing tank, settling tanks I & II, aeration pond, filtration and storage tank. The study found discrepancies in several units, particularly the grease trap, equalisation tank, aeration, filtration and storage tanks. These discrepancies are due to procedures not yet included in the SOP, delayed painting schedules and uninstalled accessories. All parameters meet the required effluent quality standards. The operating costs for wastewater treatment are estimated at Rp. 4,912/m³.